Lower bound on star arboricities of even degree crowns - Lee, Ming-Ju; Lin, Chiang (Utilitas Mathematica, 2013)
The star arboricity of a graph G is the minimum number of star forests which are needed to decompose the edges of G. For integers 1 ≤ d ≤ n, let Cn,d be the graph with vertex set {a0, ..., an-1, b0, ..., bn-1} and edge set {aibj : i = 0, ···, n - 1; j ≡ i + 1, ···, i + d (mod n)}. We call Cn,d a crown. In this paper, we investigate the lower bound on star arboricities of crowns with even degree.